Emerging Trends and Future Directions in Organic Agriculture and Environmentally-friendly Farming Practices: A Bibliometric Analysis - Muhammad Hazmi; Dyah Ayu Suryaningrum; Iskandar Umarie; Oktarina; Muh. Aniar Hari Swasono (West Science Interdisciplinary Studies, 2023)
Organic farming and eco-friendly agricultural practices have gained significant attention as sustainable alternatives to conventional agriculture. This research method employs bibliometric and keyword analysis to explore the field’s emerging trends and future directions. The co-occurrence analysis of keywords reveals prominent research themes, including organic certification, soil health, climate change resilience, agroecological approaches, biodiversity conservation, and integrated pest management. The analysis also identifies influential authors, collaboration networks, and prominent publication venues that disseminate research in sustainable agriculture. The keyword analysis highlights the literature’s focus on adoption, agricultural products, consumer behavior, and sustainable agricultural development. This research provides valuable insights for advancing knowledge, policy development, and practical applications in organic farming and eco-friendly agrarian practices to foster sustainable and environmentally friendly agricultural systems.